2014
DOI: 10.1140/epjc/s10052-014-3090-1
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the cosmic age problem in the $$R_\mathrm{h}=ct$$ R h = c t universe

Abstract: Many dark energy models fail to pass the cosmic age test. In this paper, we investigate the cosmic age problem associated with nine extremely old Global Clusters (GCs) and the old quasar APM 08279+5255 in the R h = ct universe. The age data of these oldest GCs in M31 are acquired from the Beijing-Arizona-Taiwan-Connecticut system with up-to-date theoretical synthesis models. They have not been used to test the cosmic age problem in the R h = ct universe in previous literature. By evaluating the age of the R h … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…First we have presented our subluminal model only as a possibility of thinking. The model of Melia [2]- [20] is actually flat, but in some cases it is consistent with our spatially positively curved model. Thus, we are encouraged to present our proposal as a realistic model.…”
Section: Preliminary Remarkssupporting
confidence: 85%
“…First we have presented our subluminal model only as a possibility of thinking. The model of Melia [2]- [20] is actually flat, but in some cases it is consistent with our spatially positively curved model. Thus, we are encouraged to present our proposal as a realistic model.…”
Section: Preliminary Remarkssupporting
confidence: 85%
“…It has been demonstrated that the loading of the ultrasmall Au NCs onto TiO 2 nanocrystals results in strong visible light absorption and signifi cantly increased visible light photocatalytic activity for water splitting or hydrogen generation. [ 132 ] Similarly, Au NCs loading onto BaLa 4 Ti 4 O 15 leads to signifi cantly enhanced visible light photocatalytic activity. [ 133 ] Moreover, Amal and co-workers [ 134 ] investigated the improvement of photocatalytic performance of TiO 2 by mixing metal cluaters.…”
Section: Quantum Clusters As a Catalystmentioning
confidence: 99%
“…With the continuous improvement of WGMRs in optical sensing, many novel geometric structures have appeared in recent years, such as: microdisk, [17,[116][117][118][119][120][121][122][123][124][125] microbubble, [126][127][128][129][130][131][132] microbottle, [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] microtube, [148][149][150][151][152][153][154][155][156][157][158][159][160] microcylinder, [161][162][163] etc. These new resonators are widely used in the field of phy...…”
Section: Preparation and Application Of Other Types Of Resonatorsmentioning
confidence: 99%